2013
DOI: 10.1002/pbc.24687
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of central lines in pediatric oncology patients: Early removal and patient centered outcomes

Abstract: SPs demonstrated lower removal rates and greater patient satisfaction than EVCs. These data should be considered when choosing a central line for pediatric cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
(65 reference statements)
3
12
0
1
Order By: Relevance
“…This finding was in keeping with a meta‐analysis of adult studies that identified a higher rate of thrombosis in PICC lines, particularly in adults who were critically ill or had malignancy (Chopra et al , ), although more recent data in adults have shown a lower risk of thrombosis compared with traditional CVLs in a population with acute leukaemia (Cerchione et al , ). Thrombosis occurs less frequently in association with internal lines (ports) than external tunnelled lines, such as Hickman or Broviac catheters (McClean et al , ; White et al , ; Mangum et al , ). A multicentre randomised controlled trial (RCT) in adults with malignancy, comparing complication rates between external tunnelled lines, ports and PICCs for the administration of chemotherapy, is currently ongoing [Cancer and Venous Access (CAVA); ISRCTN 44504648].…”
Section: Reducing the Risk Of Vtementioning
confidence: 99%
“…This finding was in keeping with a meta‐analysis of adult studies that identified a higher rate of thrombosis in PICC lines, particularly in adults who were critically ill or had malignancy (Chopra et al , ), although more recent data in adults have shown a lower risk of thrombosis compared with traditional CVLs in a population with acute leukaemia (Cerchione et al , ). Thrombosis occurs less frequently in association with internal lines (ports) than external tunnelled lines, such as Hickman or Broviac catheters (McClean et al , ; White et al , ; Mangum et al , ). A multicentre randomised controlled trial (RCT) in adults with malignancy, comparing complication rates between external tunnelled lines, ports and PICCs for the administration of chemotherapy, is currently ongoing [Cancer and Venous Access (CAVA); ISRCTN 44504648].…”
Section: Reducing the Risk Of Vtementioning
confidence: 99%
“…These data also were not included in the review. We were unable to ascertain the number of catheter days in 23 studies, [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82]84,85,92,97,99,122 which excluded their data from contributing to the meta-analysis reporting failure and complications per 1000 catheter days. Because of a lack of data, the rate of CVAD failure per 1000 catheter days for nontunneled, percutaneous CVADs could not be estimated.…”
Section: Study Qualitiesmentioning
confidence: 99%
“…Twelve studies 59,61,66,67,72,76,82,83,89,97,105,121 described the outcome of CVADassociated BSI without the clarity and rigor of benchmarked standards, which meant that their CVAD-associated BSI data were not included in the review. Two studies 30,116 provided combined "all-type" infection or mechanical failure outcomes, instead of providing separated local and systemic infection, occlusion, and dislodgement data.…”
Section: Study Qualitiesmentioning
confidence: 99%
“…Risk of line-associated thrombosis has been reported to be higher in relation to an external device. [11][12][13] A small proportion of (adult) centers are using PICCs and, although not formally evaluated in a pediatric setting, these are associated with a higher rate of thrombosis in adults with malignancy. 14 The number of PICC-associated thrombotic events reported in the MRC UKALL 2003 trial led to an alert being released by the Chief Investigator recommending that PICCs should not be used (personal oral communication, A. Vora).…”
Section: Discussionmentioning
confidence: 98%